Intended Coping Responses to Cancer Symptoms in Healthy Adults: The Roles of Symptom Knowledge, Detection Behavior, and Perceived Threat - Ruiter, Robert A.C.; de Nooijer, Jascha; van Breukelen, Gerard; Ockhuysen-Vermey, Caroline F.; de Vries, Hein (Cancer epidemiology, biomarkers & prevention, 2008)
Background: To date, the causal effects of the knowledge of cancer-related symptoms and detection behavior on coping with cancer-related symptoms have not been identified. Therefore, the current study explored the effects of active or passive detection of supposedly well-known or less-known cancer-related symptoms on intended coping responses. In addition, we were interested in the extent to which these effects are driven by heightened perceptions of threat. Methods: In an experimental study using a 2 × 2 within-subject design, 221 Dutch adults from the general population responded to a survey study sent to their homes (18.4% response). They were asked to read scenario information about four cancer-related symptoms that were ( a ) well known or less known and ( b ) actively or passively detected (e.g., self-examination versus unusual blood loss). The authors measured intended coping responses to the detection of cancer-related symptoms as either adaptive (e.g., visiting a general practitioner) or maladaptive (e.g., denial of the symptom). Results: As expected, the findings revealed that well-known symptoms resulted in more anticipated adaptive coping and less anticipated maladaptive coping than less-known symptoms. Unfortunately, the findings also suggest that the active as opposed to passive detection of cancer symptoms (e.g., self-examination versus unusual blood loss) is likely to result in more maladaptive coping. These effects were mediated by heightened perceptions of threat. Conclusions: Future health education programs that aim to motivate people to be more active in the early detection of cancer symptoms should first focus on increasing people's knowledge about the early warning signs of cancer. (Cancer Epidemiol Biomarkers Prev 2008;17(4):818–26)